Analogical classification in formal grammar - Guzmán Naranjo, Matias (Empirically Oriented Theoretical Morphology and Syntax, 2019)
The organization of the lexicon, and especially the relations between groups of lexemes is a strongly debated topic in linguistics. Some authors have insisted on the lack of any structure of the lexicon. In this vein, Di Sciullo & Williams (1987: 3) claim that "[t]he lexicon is like a prison - it contains only the lawless, and the only thing that its inmates have in commonis lawlessness". In the alternative view, the lexicon is assumed to have a rich structure that captures all regularities and partial regularities that exist between lexical entries.Two very different schools of linguistics have insisted on the organization of the lexicon.